Proximal predictors of change in quality of life at older ages. Issue 6 (6th August 2010) - Webb, Elizabeth; Blane, David; McMunn, Anne; Netuveli, Gopalakrishnan
Abstract : Objective: To investigate whether changes in health, social and economic circumstances predict change in quality of life (QoL) at older ages. Design: Secondary analysis, using multiple regression analyses, of waves 1 and 3 of the English Longitudinal Study of Ageing. Setting: England, 2002–6. Participants: A nationally representative sample of non-institutionalised adults aged over 50 years living in England with non-missing data for the variables of interest (N=4848). Main Outcome Measure: QoL in 2006, with reference to QoL in 2002, both measured using the CASP-19 score. Results: Mean QoL decreased over the 4 years, with becoming depressed (β −0.12) and developing difficulties with activities of daily living (β −0.08) contributing to this decrease. Improvements in family relationships (β 0.10), the neighbourhood (β 0.08) and perceived financial position (β 0.07) each counteracted the decline in QoL. Initial QoL strongly predicted QoL at follow-up (β 0.46). Regression models explained 59% of variation in QoL, and there were small differences between age and gender groups. Conclusions: The maintenance of good QoL in older aged people is enabled by the avoidance of depression, maintenance of physical function, good neighbourhood standards, family relationships and financial circumstances.